The Effect of Extra Educational Elements on the Confidence of Undergraduate Dental Students Learning to Administer Local Anaesthesia - Mats Sjöström; Malin Brundin (Dentistry Journal, 2021)
Local anaesthesia is taught early in the practical part of dental programs. However, dental students express uncertainty and concern before their practical training in local anaesthesia. The aim of this study was to evaluate how extra educational elements in the teaching of local anaesthesia affect students’ confidence using local anaesthesia. The students were divided into three groups (A, B and C). Group A received the same education that was used the previous year (i.e., four hours of theoretical lectures followed by four hours of practical exercises performed on a fellow student). Group B did their practical training on fellow students in groups of three, with each student taking turns performing, receiving and observing the procedure. Group C received training using an anatomically correct model before their practical training on a fellow student. After each training step, the students completed a questionnaire about their confidence administering local anaesthesia. The students experienced a significant increase in confidence after each educational step. Combining theory and practical instruction, including the use of anatomically correct models and peer instruction, improved students’ confidence in administering local anaesthesia. The greatest increase in confidence was in the students placed in groups of three where each student performed, received and observed the procedure.